Local User-Producer Interaction in Innovation and Export Performance of Firms - Christian Rammer; Marian Beise (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2003)
There is ample evidence that user-producer interaction is an important factor for successful innovations. It is often claimed that user-producer interaction is most effcient in close proximity. On the other hand, innovations are a major determinant for the export performance of firms. Does this mean that intense local user-producer interaction always leads to exports? In contrast to this reasoning international marketing studies stress the problem of responsiveness to local preferences. In order to generate global innovation, an international firm should look for the global common denominator of national preferences. This paper investigates the question to what extend local demand is able to induce innovations that are export effective. We investigate data from the ZEW Innovation survey of 4,786 firms in the manufacturing and service industries. These firms were asked about the sources of their innovation and their exporting activities. We find evidence that the export orientation of the domestic market of innovators such as and the degree of competition stimulate export success. For multinational firms these results are important as well, because they can assess country markets in terms of the leverage effect of domestic demand and market conditions to generate global innovations.
Keywords: C53; F14; O31; L80; 330; Export Performance; Innovation Activities; User Producer Interaction; Innovation; Lieferanten-Kunden-Beziehung; Export; Internationaler Wettbewerb; Deutschland